2005
DOI: 10.1186/1471-2482-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal surgical site infections: incidence and risk factors at an Iranian teaching hospital

Abstract: BackgroundAbdominal surgical site infections are among the most common complications of inpatient admissions and have serious consequences for outcomes and costs. Different risk factors may be involved, including age, sex, nutrition and immunity, prophylactic antibiotics, operation type and duration, type of shaving, and secondary infections. This study aimed to determine the risk factors affecting abdominal surgical site infections and their incidence at Imam Khomeini, a major referral teaching hospital in Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
67
5
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 5 publications
20
67
5
7
Order By: Relevance
“…Some other reports are in agreement with the finding in this study. 13,16 Position of patient on operation list did not influence the rate of infection in this study. This refers to the sequence in which operations are taken during surgery sessions.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Some other reports are in agreement with the finding in this study. 13,16 Position of patient on operation list did not influence the rate of infection in this study. This refers to the sequence in which operations are taken during surgery sessions.…”
Section: Discussioncontrasting
confidence: 45%
“…This report is at variance with the finding from Iran. 13 In the present study, obesity was associated with SSI to the extent that an obese patient was five times more likely to be infected than non-obese patients. a researcher at Iran reported the same finding.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…13 The variables associated with the risk of SSI were duration of antibiotic prophylaxis, age, elevated American Association of Anaesthetists (ASA) score, prolonged preoperative hospital stay, duration of operation, emergency surgery, and sex. [14][15][16] Bivariate analysis between leucocyte count and SSI showed that leucocyte count had no significant relationship with SSI. An abnormal leucocyte count had the possibility of 3.295 times higher than the normal one.…”
mentioning
confidence: 97%
“…Surgical site infection defined as the presence of at least one of the following criteria: Pain or tenderness, localized swelling, erythema, localized heat, purulent drainage, accompanied by the fever and anorexia with a positive culture from the superficial incision or subcutaneous tissue which occurs within 30 days after the surgery (1). There has been estimated that, about 234 million operations performed annually throughout the world (2).…”
Section: Contextmentioning
confidence: 99%